OP0204 LUPUS COMPREHENSIVE DISEASE CONTROL IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS: APPLICATION OF A NEW INDEX. (2nd June 2020) - Ceccarelli, F.; Olivieri, G.; Dominici, L.; Celia, A. I.; Cipriano, E.; Garufi, C.; Mancuso, S.; Natalucci, F.; Orefice, V.; Perricone, C.; Pirone, C.; Pacucci, V. A.; et al.
Abstract : Background: The main outcomes in SLE patients management are represented by the remission achievement and chronic damage prevention. Even though activity and damage are intimately connected, to date indices including both these outcomes are not available. Objectives: In the present study, we aimed at assessing the application of a new index, the Lupus comprehensive disease control ( LupusCDC ), including disease activity and chronic damage progression. Methods: We performed a longitudinal analysis, including SLE patients according to ACR 1997 criteria, followed-up in the period between January 2014 and December 2018, and with at least one visit per year. Disease activity was assessed by SLE Disease Activity Index 2000 (SLEDAI-2K) and three different remission levels were evaluated, as reported in Table 1 (1). Chronic damage was registered according to SLICC damage index (SDI). All the patients were evaluated at baseline (T0) and every 12 months (T1, T2, T3, T4). At each time-point, we calculated the prevalence of LupusCDC, defined as remission achievement plus absence of chronic damage progression in the previous one year. We calculated this outcome including separately the different remission levels. Results: According with inclusion criteria, 172 SLE patients were evaluated in the present analysis [M/F 16/156, median age 49 years (IQR 16.7), median disease duration 180 months (IQR 156)]. At first assessment, we observed a mean±SD SDI value of 0.7±1.1. In details, 56 patients (32.5%) showed damage in at least one organ/system and the presence of damage was significantly associated with age (p<0.0001, r=0.3) and disease duration (p=0.0003, r=0.3). During the follow-up, we observed a significant increase in SDI values compared with T0 (T1: mean±DS 0.8±1.3, p<0.0001; T2: 0.8±1.4, p<0.0001; T3: 0.9±1.4 p=0.0001; T4: 1.0±1.5 p<0.0001). In figure 1A and 1B we reported the proportion of patients achieving the different levels of remission and LupusCDC, respectively. In particular, the LupusCDC definition including CR was the most frequently detected in all time-points evaluated (T1: 18.0%; T2: 31.9%; T3: 27.9%; T4: 24.4%), with a significant difference at T2 [LupusCDC(CR) versus LupusCDC(ClR-GCoff), p=0.0002; LupusCDC(CR) versus LupusCDC(ClR-GCon) p=0.0002)], T3 [LupusCDC(CR) versus LupusCDC(ClR-GCoff), p=0.03; LupusCDC(CR) versus LupusCDC(ClR-GCon) p=0.006], T4 [LupusCDC(CR) versus LupusCDC(ClR-GCon), p=0.002]. No significant differences were found when comparing the prevalence of different remission levels and the prevalence of LupusCDC including the corresponding remission. Conclusion: In the present analysis we proposed for the first time a new index including disease activity and chronic damage, in order to evaluate the proportion of SLE patients reaching a comprehensive disease control. We found that CR is most frequently associated with the absence of damage progression. References: [1]Zen M et al. Ann Rheum Dis 2017. Disclosure of Interests: Fulvia Ceccarelli: None declared, Giulio Olivieri: None declared, Lorenzo Dominici: None declared, Alessandra Ida Celia: None declared, enrica cipriano: None declared, Cristina Garufi: None declared, Silvia Mancuso: None declared, Francesco Natalucci: None declared, Valeria Orefice: None declared, Carlo Perricone: None declared, Carmelo Pirone: None declared, viviana antonella pacucci: None declared, Francesca Morello: None declared, Simona Truglia: None declared, Francesca Miranda: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, cristiano alessandri Grant/research support from: Pfizer, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi